The relevance of music information representation metadata from the perspective of expert users - Barros, Camila Monteiro de; Café, Lígia Maria Arruda (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The general goal of this research was to verify which metadata elements of music information representation are relevant for its retrieval from the perspective of expert music users. Based on a bibliographical research, a comprehensive metadata set of music information representation was developed and transformed into a questionnaire for data collection, which was applied to students and professors of the Graduate Program in Music at the Federal University of Rio Grande do Sul. The results show that the most relevant information for expert music users is related to identification and authorship responsibilities. The respondents from Composition and Interpretative Practice areas agree with these results, while the respondents from Musicology/Ethnomusicology and Music Education areas also consider the metadata related to the historical context of composition relevant.Keywords: Information representation. Metadata. Music information.Link para o texto completo (PDF)http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/2077/1772